Correlation between compressibility and basic soil parameters - Mohd. Shahril Saedon, 1982-, author; Aminaton Marto, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017